Maritime green supply chain management (MGSCM) and financial performance : a mediating effect of energy efficiency and low carbon performance - Muhamad Fairuz, Ahmad Jasmi (2019)
As awareness and consciousness regarding the negative ecological impacts that industry bring to the environment increases, more organizations around the globe have motivated in establishing sustainable operations. As a result, a cross-disciplinary interest in the field of supply chain management (SCM) and green supply chain management (GSCM) has grown amongst scholars and practitioners in recent years due to environmental issues, deteriorating raw materials and excess of waste production. However, there has been little work done in developing and incorporating green measures into the existing maritime supply chain literature. Only a handful of articles has been published in the last decade on the green concept in maritime context literature. The aim of this study is thus, to address this challenge by empirically developing and testing maritime green supply chain management (MGSCM) measures and performance for the maritime supply chain. Based on an extensive literature review, eight research questions were proposed for this study to address current gaps in the body of knowledge. Hence, this study has proposed five (5) MGSCM variables and three (3) performance constructs that can be used by organizations to measure MGSCM impact on the maritime organization. However, two (2) out of three (3) constructs which consists energy efficiency performance (EEP) and low carbon performance (LCP) will act as mediating variables to study inter-relationship that might be influenced the single performance outcome construct of financial performance (FP). An online survey was administrated to various maritime supply chain companies in Malaysia. One hundred sixty (160) sets of questionnaires were analysed using the partial least squares method through structural equation modelling (SEM) with Smart PLS software and IBMSPSS software for descriptive analysis. The findings confirmed that from the maritime supply chain perspective, certain MGSCM practices (such as GICS and GSIP) facilitated financial performance outcome. The results also showed support for the hypotheses that EEP and LCP mediate the effect of GICS, GVALS, and SDC on financial performance. To a certain extent, the findings of the study validated the robustness of the MGSCM framework based on the extended natural resource-based view (NRBV) and GSCM theory to study the sustainability impact from maritime supply chain perspective. Finally, this study has presented a practical suggestion for practitioners and policymakers which highlighted a need to adopt green practices in the supply chain operation to achieve sustainable operation and long-term competitive advantage.